Unlocking cellular traffic jams: olive oil-mediated rescue of CNG mutant channels - Avalos-Hernandez, Angeles; Juarez-Navarro, Karina; Ruiz-Baca, Estela; Meneses-Morales, Ivan; Espino-Saldaña, Edith; Martinez-Torres, Ataulfo; Lopez-Rodriguez, Angelica (Frontiers in Pharmacology, 2024)
One of the reasons to suggest olive oil consumption for a healthy life is its potential to induce robust lipidomic remodeling through membrane modification by dietary lipids. This remodeling might, in turn, modulate essential lipid-protein interactions while maintaining accurate transmembrane protein/domain orientation. Oleic acid, the primary compound in olive oil, has been suggested as a modulator of ion channel function. In this study, we explored whether this lipid could rescue the trafficking of mutated transmembrane proteins. In our initial approach, we supplemented the cell culture medium of HEK-293 cells expressing cyclic nucleotide channels tagged using green fluorescent protein (CNG-GFP) with olive oil or oleic acid. In addition to wildtype channels, we also expressed R272Q and R278W mutant channels, two non-functional intracellularly retained channels related to retinopathies. We used fluorescence microscopy and patch-clamp in the inside-out configuration to assess changes in the cell localization and function of the tested channels. Our results demonstrated that olive oil and oleic acid facilitated the transport of CNG R272Q mutant channels towards the plasma membrane, rendering them electrophysiologically functional. Thus, our findings reveal a novel property of olive oil as a membrane protein traffic inductor.